Penggunaan TOGAF ADM 9.1 Pada Perancangan Enterprise Architecture Fungsi Layanan Beasiswa Universitas Kristen Maranatha - Rina Adrianti; Niko Ibrahim (Jurnal Teknik Informatika dan Sistem Informasi, 2019)
In Indonesia, which poverty rates reaching 9.82% in March 2018, education cost is a barrier for sections of societies with low household income. So that the availability of scholarships is a solution. Based on this, Maranatha Christian University provides tuition assistance in the form of scholarships for students with several categories, which are managed by Student Welfare Sector, under the supervision of the Directorate of Student Affairs. The problem in managing the scholarship is that there is no adequate system. The goal is this research is to design a business strategy and information system strategy to achieve harmony based on present and future needs. TOGAF Framework, the enterprise architecture method is chosen to provide an effective and efficient solution from the business architecture phase, information system architecture phase, and technology architecture phase. The result of this research is in the form of TOGAF ADM artifact, as the blueprint architecture and IT development recommendations that are expected to be a guide in the development of scholarship services at Maranatha Christian University.